Autophagic Organelles in DNA Damage Response - Kim, Jeongha; Lee, Sungmin; Kim, Hyunwoo; Lee, Haksoo; Seong, Ki Moon; Youn, HyeSook; Youn, BuHyun (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is an important subcellular process involved in the maintenance of cellular homeostasis via the degradation of cargo proteins and malfunctioning organelles. In response to cellular stresses, such as nutrient starvation, infection, and DNA-damaging agents, autophagy is activated to reduce the damage and restore cellular homeostasis. One of the responses to cellular stresses is the DNA damage response (DDR), a network of intracellular pathways that senses and repairs damaged DNA. Proper regulation of these pathways is crucial for preventing diseases. The involvement of autophagy in the repair and elimination of DNA aberrations is essential for cell survival and recovery to normal conditions, highlighting the importance of autophagy in the determination of cell fate. In this review, we summarized the latest information about autophagic recycling of mitochondria, endoplasmic reticulum (ER), and ribosomes (called mitophagy, ER-phagy, and ribophagy, respectively) in response to DNA damage. In addition, we have described the key events necessary for a comprehensive understanding of autophagy signaling networks. Finally, we have highlighted the importance of the autophagy activated by DDR and appropriate regulation of autophagic organelles, suggesting insights for future studies. Especially, DDR from DNA-damaging agents such as IR (ionizing radiation) or anticancer drugs, induces damage to subcellular organelles and autophagy is the key mechanism for removing impaired organelles.